Pre-stressed rubber material constant estimation for resilient wheel application. (November 2017) - Šulc, Petr; Pešek, Luděk; Bula, Vítězslav; Cibulka, Jan; Boháč, Tomáš; Tašek, Hubert
Highlights: Methodology and results of the complex modulus estimation of rubber segments pressed between the disk and the rim of a rubber-damped railway wheel. Method proposed and validated at rubber constant identification on the case of the steel beam with rubber layer. Results of tuned rubber material constants, i.e. the modulus of elasticity and a loss factor, of the rail rubber segments are very valuable for prediction of modal behavior of the new resilient wheels and they are qualitatively in accordance with the behavior of hard synthetic rubbers. Abstract: This paper describes the methodology and results of the complex modulus estimation of rubber segments pressed between the disk and the rim of a rubber-damped railway wheel. The solution comes out from the method proposed and validated at rubber constant identification on the case of the steel beam with rubber layer. In the vicinity of eigenfrequency its dependence to Young modulus is quasilinear and can be solved effectively by the gradient method. The similar behavior showed itself also for dependence of the modal damping constant on the damping coefficient. The ascertained results of tuned rubber material constants, i.e. the modulus of elasticity and a loss factor, of the rail rubber segments are very valuable for prediction of modal behavior of the new resilient wheels and they are qualitatively in accordance with the behavior of hard synthetic rubbers.